TEKNIK DETEKSI DNA/GENE TARGET TERHADAP PATOGEN PENYEBAB PENYAKIT TANAMAN - HARYUNI, HARYUNI (JURNAL ILMIAH AGRINECA, 2008)
Applications for detecting and Quantifying Transcripts to quantifyng viruses, pathogen detection, gene expression, drug theraphy, DNA damage, Immune response, genotyping.Methods in common use for detecting/quantifying transcrips are: 1) Northern blothing and in situ hybridization, 2) RNAse protection assays, 3)cDNA microarrays, 4) Reverse transciption-polymerase chain reaction.